EVALUATION OF RHIZOSPHERIC FUNGI FROM ACID SOILS OF JHARKHAND ON PHOSPHATE SOLUBILIZATION - S. K. NAIK; S. MAURYA; KUMAR, RITESH; J. S. CHOUDHARY; DAS, BIKASH; S. KUMAR (The Bioscan, 2012)
Phosphate solubilising fungi (PSF) were isolated from various pea, mango and cauliflower-rhizosphere soils of Jharkhand. Three efficient phosphate solubilising fungi were selected based on their ability to form clear zone on Pikovskaya’s agar medium. Incubation experiment was conducted with 3 sources of inorganic phosphorus imposed on 3 isolated strains of native phosphate solubilizing fungi. Among the PSF, Aspergillus niger produced the highest phosphate solubilization zone and colony growth in all the sources of inorganic phosphorus compared to Trichoderma viride and Penicillium chrysogenum. Aspergillus niger attained the highest phosphorus solubilization efficiency and phosphorus solubilization index after 120h of incubation in tricalcium phosphate, 96h of incubation in both potassium dihydrogen phosphate and ferric phosphate source. Trichoderma viride and Penicillium chrysogenum attained highest peak of phosphorus solubilization efficiency and phosphorus solubilization index after 144 and 120h of incubation in tricalcium phosphate and potassium dihydrogen phosphate, respectively. In ferric phosphate source, Trichoderma viride and Penicillium chrysogenum attained highest peak of phosphorus solubilization efficiency and phosphorus solubilization index after 96 and 120h of incubation, respectively. Aspergillus niger was found to be the most efficient in solubilizing phosphate from the inorganic sources at the earliest followed by Trichoderma viride and Penicillium chrysogenum